Leaders, Followers, and Risk Dynamics in Industry Equilibrium - Murray Carlson; Engelbert Dockner; Adlai Fisher; Ron Giammarino (Verein für Socialpolitik, 2010)
We study own and rival risk in a dynamic duopoly with a homogeneous output good. A competitor's options to adjust capacity reduce own-firm risk through a simple hedging channel. For example, if a rival possesses a growth option, an increase in industry demand directly enhances current profits but also encourages value-reducing competitor expansion. As a consequence, when a leader and a follower emerge in equilibrium, risk dynamics depart substantially from previously-studied simultaneous move benchmarks. Own-firm and competitor required returns tend to move together through contractions and oppositely during expansions, providing testable new empirical predictions.
Keywords: G31; D43; D92; 330; Growth options and industry risk; asset pricing and investment decisions; risk dynamics in oligopolistic industries